Classification and literature review on the integration of simulation and optimization in maritime logistics studies. (3rd October 2021) - Zhou, Chenhao; Ma, Ning; Cao, Xinhu; Lee, Loo Hay; Chew, Ek Peng
Abstract: The traditional maritime logistics industry is facing an industry transformation created by technology development. Along with industry transformation, the maritime logistics research field is also facing new challenges and opportunities. It is found that using simulation or optimization alone to solve maritime logistics decision problems has some drawbacks. Instead, a trend of integrating the two methods is becoming more and more popular in recent literature. However, an in-depth and systematic literature review is absent. Thus, this article reviews 107 papers on the integration of simulation and optimization for the maritime logistics studies published in the last two decades. Five modes of integration are identified based on how the two methods interact. For each mode, a detailed literature review on different maritime logistics processes is presented, covering terminal operation, shipping line operation, and hinterland transport operation. Lastly, how the integration of simulation and optimization could contribute to the next generation maritime systems is discussed with future research directions given.